2014
DOI: 10.1093/mnras/stu2331
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismic inference on rotation, gyrochronology and planetary system dynamics of 16 Cygni

Abstract: The solar analogs 16 Cyg A and 16 Cyg B are excellent asteroseismic targets in the Kepler field of view and together with a red dwarf and a Jovian planet form an interesting system. For these more evolved Sun-like stars we cannot detect surface rotation with the current Kepler data but instead use the technique of asteroseimology to determine rotational properties of both 16 Cyg A and B. We find the rotation periods to be 23.8 • , for A and B respectively. Together with these results we use the published mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 55 publications
4
85
0
Order By: Relevance
“…From spectroscopy with high signal-to-noise ratio of the 10 m Keck 1 telescope and HIRES echelle spectrograph, Schuler et al (2011) determined the abundance of 15 heavy elements in both stars and found them indistinguishable. On the other hand, Ramírez et al (2011) andTucci Maia et al (2014) claimed that 16 Cygni A is slightly more metal rich than 16 Cygni B based on spectra with high resolution Ramírez et al (2011); (c) Schuler et al (2011); White et al (2013), seismic determination; (e) White et al (2013), interferometric determination; ( f ) Tucci Maia et al (2014); (g) Metcalfe et al (2012); (h) Davies et al (2015); (i) King et al (1997); ( j) Deliyannis et al (2000); (k) Cochran et al (1997).…”
Section: Observational Constraintsmentioning
confidence: 99%
“…From spectroscopy with high signal-to-noise ratio of the 10 m Keck 1 telescope and HIRES echelle spectrograph, Schuler et al (2011) determined the abundance of 15 heavy elements in both stars and found them indistinguishable. On the other hand, Ramírez et al (2011) andTucci Maia et al (2014) claimed that 16 Cygni A is slightly more metal rich than 16 Cygni B based on spectra with high resolution Ramírez et al (2011); (c) Schuler et al (2011); White et al (2013), seismic determination; (e) White et al (2013), interferometric determination; ( f ) Tucci Maia et al (2014); (g) Metcalfe et al (2012); (h) Davies et al (2015); (i) King et al (1997); ( j) Deliyannis et al (2000); (k) Cochran et al (1997).…”
Section: Observational Constraintsmentioning
confidence: 99%
“…Initial indications of anomalous rotation and magnetic activity in old field stars relied on asteroseismic properties from [21], which were based on an analysis of only 9 months of data ( [22]). Kepler completed its primary mission in 2013, but the large samples of multi-year observations posed an enormous data analysis challenge that has only recently been surmounted ( [23][24][25]). The longer data sets improved the signal-to-noise ratio (S/N) of the power spectrum for fainter stars with previously marginal detections, and yielded additional oscillation frequencies for the brighter targets.…”
Section: Asteroseismology With Keplermentioning
confidence: 99%
“…due to rotation and the inclination angle i of the star (see, e. g., Chaplin et al 2013;Huber et al 2013b;Lund et al 2014;Davies et al 2015). Figure 5 shows the splitting versus inclination correlation map from the MCMC fit of EPIC 206009487.…”
Section: Seismic Parameter Estimationmentioning
confidence: 99%